RESILIENSI IBU YANG MEMILIKI ANAK DOWN SYNDROME DI SEKOLAH LUAR BIASA (SLB) NEGERI 1 SUMBAWA - Asfiah Nursilmi Kaffah; Yossy Dwi Erliana; Ivon Arisanti (JURNAL PSIMAWA, 2019)
This study aims to determine the resilience ability of mothers who have Down Syndrome children at Sumbawa Besar Special School. This study uses a descriptive qualitative approach. The determination of the research subjects was carried out by using purposive sampling. The variable was the resilience of mothers who had Down Syndrome children and there were 3 mothers as the subjects. This research used interview, observation and documentation methods. The results of this study indicate that of the three subjects only one had resilience. While the other two subjects did not fulfill several aspects of resilience. R subjec fulfills the seven aspects in resilience while L subject does not fulfill aspects of optimism and causal analysis, H subject does not fulfill the regulatory aspects of emotion, impulse control, empathy and causal analysis. In general, not all mothers with Down Syndrome children have resilience abilities, some are capable and some are in the process of achieving resilience, especially from different levels of education, economy, family support and the level of religiosity.